Proceedings of the 53rd ACM Technical Symposium on Computer Science Education 2022
DOI: 10.1145/3478431.3499328
|View full text |Cite
|
Sign up to set email alerts
|

Experience Report on the Use of Breakout Rooms in a Large Online Course

Abstract: In this paper, we present our experience with the use of breakout rooms in a second year undergraduate Software Design course at a large North American institution. Following the switch to remote instruction during the coronavirus pandemic, we revamped our in-person Software Design course to be delivered as a flipped online course, making extensive use of in-lecture exercises completed during breakout rooms. We report on the structure and logistics of this lecture design (for a large class of 300+ students). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 20 publications
4
18
0
Order By: Relevance
“…If the students in a group are not active and no student partakes in the group discussion, they only get stuck there and learn nothing from the breakout rooms. A study by Sharmin and Zhang (2022) found that students enjoyed the use of BRs as long as they actively participated in doing the assigned tasks.…”
Section: Zoom Breakout Rooms In Online Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…If the students in a group are not active and no student partakes in the group discussion, they only get stuck there and learn nothing from the breakout rooms. A study by Sharmin and Zhang (2022) found that students enjoyed the use of BRs as long as they actively participated in doing the assigned tasks.…”
Section: Zoom Breakout Rooms In Online Learningmentioning
confidence: 99%
“…Despite a large body of research investigating the uses of Zoom application for online learning and its benefits across disciplines (Correia et al, 2020;Sharmin & Zhang, 2022;Venton & Pompano, 2021) and in ELT (English Language Teaching) in particular, there is a paucity in the studies on the use of Zoom to enhance self-efficacy. In the ELT context, the use of Zoom and its BRs was responded positively by students (Bamidele, 2021), increased learners' interactions and engagement (Kohnke & Moorhouse, 2022), increased attendance and speaking participation (Lee, 2021;Nisa et al, 2021), and developed creativity (Putri & Yosintha, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Two very recent studies have aimed to start closing this gap. Sharmin and Zhang (2022) looked at weekly and end of term feedback from a class of 330 students and found a more mixed response from students, with many expressing positive feelings towards breakout room usage, but an average of 47% of students each week expressing negative feelings. In Tsihouridis et al's (2021) study of 327 students, a more positive overall response was identified particularly in giving the opportunity to communicate and discuss.…”
Section: Student Conceptionsmentioning
confidence: 99%
“…However, it also identified those in their first year of study (freshmen) were more content with the use of breakout rooms due to the social benefits they brought than those in later years of study. Both of these studies also identified a participation challenge, with the identification of student frustration with non-participative group members (Sharmin and Zhang 2022;Tsihouridis et al 2021).…”
Section: Student Conceptionsmentioning
confidence: 99%
See 1 more Smart Citation